Online education and improvement of caring behaviors of nurses in pediatric wards: a quasi-experimental study - Elnaz Monemi; Monirsadat Nematollahi (BMC, 2023)
Abstract Background Nurses working in pediatric wards should communicate with children well and have appropriate caring behaviors according to the age of their patients, so distance education is very suitable for them due to its availability. This study aimed to determine the effect of online education on the principles of pediatric nursing care on the caring behaviors of nurses working in pediatric wards. Methods This interventional (quasi-experimental) study used a simple random method to select 70 nurses working in pediatric wards and pediatric intensive care units in Kerman. The nurses in the intervention group received online training in the sky room three days a week, while nurses in the control group received routine pediatric care. The study instruments were the demographic information questionnaire and the Caring behaviors Questionnaire, which were completed by two groups before and one month after the intervention. Data were analyzed with SPSS 25. The significance level was set at P < 0.05. Results The independent samples t-test indicated no significant differences in the mean scores of care behaviors between the intervention (256.61 ± 5.16) and control groups (257.52 ± 3.99) before the intervention (P = 0.23) but indicated a significant difference in the mean scores of caring behaviors between the intervention (275.69 ± 6.52) and control groups (254.21 ± 3.15) after the intervention. Therefore, online education increased the score of caring behaviors in the intervention group. Conclusion Distance education had an impact on the caring behaviors of nurses in pediatric wards and we recommend the use of e-learning to improve the caring behaviors and the quality of care of nurses.